Analysis of teams` corner kicks defensive strategies at the FIFA World Cup 2018 - Kubayi, A.; Larkin, P. (International Journal of Performance Analysis in Sport, 2019)
The aim of this study was to analyse corner kick defensive strategies during the 2018 FIFA World Cup. A total of 600 corner kicks from all 64 matches in the tournament were obtained from the InStat database and analysed. Data were analysed and reported as frequency counts and percentages. Chi-square test for independence (Chi2) used to test associations between key performance indicators. Results showed that 22 goals (3.7% of all corners kicks) were conceded from corner kicks. Teams conceded more goals using a zonal marking strategy (6.0%) compared to a mixed marking strategy (3.7%). There was a significant association between types of corner kicks and defensive outcomes (Chi2 = 111.30,V = 0.57). Most goals were conceded from inswing corner kicks (4.6%) compared to short (3.3%) and outswing (3.1%) corner kicks. Seventeen (3.9%) goals were conceded from corners when there were no players on the goal line. Most goals came from the centre (7.0%) and the first goalpost (3.5%). These findings highlight potential strategies soccer coaches may employ for an effective defensive set-up against corners, such as employing a mixed marking method, having players positioned on the goalposts and being aware of the attacking threat posed by short corner kicks.